Food Hubs and Short Food Supply chain, Efforts to Realize Regional Food Distribution Center - Heru Winarno; Tomy Perdana; Yuanita Handayati; Dwi Purnomo (International Journal of Supply Chain Management, 2020)
Abstract— Agricultural development plays a role in providing food supply, maintaining food scarcity and maintaining food prices so as not to fluctuate and evenly distribute food, becoming a major problem in each region. Banten Province with regional potentials that have a surplus of food products and a wide area that is adequate has the potential to develop a food distribution center. The aim of a food distribution center is to meet food supply chain chain throughout the region, avoid food scarcity, stabilize food prices and maintain price disparities thus they can be properly met. The role of food hubs is to aggregate, distribute and market food at the farmer, trader level, and to function the role of the BUMD in realizing the operation of the food distribution center. Short food supply chain chains cut costs of crop production in farmers, food distribution costs and transportation costs from farmers to distribution centers. Government policies through relevant local government agencies must be able to move the role of stakeholders in this case farmers, traders, distributors, transportation services in realizing the operation of the food distribution center to provide food procurement services and able to provide welfare levels, especially small farmers as producers in the supply chain of food products.